Brain Metastases Unresponsive to Immunotherapy Detected by 18F-FDG-PET/CT in a Patient with Melanoma - Rosa Fonti; Sara Pellegrino; Ciro Gabriele Mainolfi; Elide Matano; Silvana Del Vecchio (Diagnostics, 2020)
Recently, newer therapies such as immunotherapy have been increasingly used in the treatment of several tumors, including advanced melanoma. In particular, several studies showed that the combination of ipilimumab, an anti-Cytotoxic T-lymphocyte Associated Protein 4 (CTLA-4) monoclonal antibody and nivolumab, an anti-Programmed Death 1 (PD-1) monoclonal antibody, leads to improved survival in patients with metastatic melanoma. Despite that, immunotherapeutic agents may not reach therapeutic concentration in the brain due to the blood–brain barrier. We report the case of a 50-year-old man with advanced melanoma who underwent whole-body 18F-FDG-PET/CT before and after treatment with immunotherapy showing resistant brain metastases confirmed by subsequent MRI of the brain. Moreover, 18F-FDG-PET/CT was able to detect an immune-related adverse event such as enterocolitis that contributed to the worsening of patient conditions. This case shows how a whole-body methodology such as 18F-FDG-PET/CT can be useful in identifying melanoma cancer patients unresponsive to immunotherapy that may benefit from traditional palliative therapy in the effort to improve their quality of life.